A SEMANTIC ANALYSIS OF ENTAILMENT APPLIED IN SONG LYRICS BASED ON NIKI’S RECENT FULL ALBUM: “NICOLE” - Aolia Maelani; Suci Budiwaty (UG Journal, 2023)
The topics discussed in this research were types of entailment in song lyrics of Niki’s full album, “Nicole”, and the order of entailment applied. The objectives were to identify the types of entailment and to describe the orders of entailment applied in the song lyrics in Niki’s recent full album “Nicole”. This research used a descriptive qualitative approach that employed the theory of Fromkin, Rodman, and Hyams (2011); Lakoff and Johnson (2003); and Yule (2000). The data found in this research were 43 data within the song lyrics sentences and the results showed there were 30% (13 data) for one-way entailment; negative entailment 30% (13) of the data; mutual entailment 26% (11 data); meanwhile metaphorical entailment percentages only 14% (6 data). A significant void exists in the use of entailment orders. Background entailment occurred frequently in the data used, as it took 95% of the percentage which was equivalent to 41 data, while in the other orders; foreground entailment reached only 5% or two of the data.